(untitled) (The Peerian Journal, 2025)
The study deals with the influential significance of tourism advertising according to ultimatum of archaeological tourism in Iraq, noting the slow development in this essential sector and the minimal tourism interest despite the wealth of tourism assets in the country. Most information is gathered by distributing a survey to a travel model of tourism and travel agencies among the city of Baghdad and other provinces, with 50 participants, resulting in 30 valid questionnaires being returned for statistical examination. One employed the SPSS / V23 software to analyze the responses from the survey. By evaluating the study hypotheses, one found that tourism marketing significantly contributes to enhancing tourism demand within the examined travel and tourism companies. The study also highlights the importance of leveraging the elements of the tourism marketing mix and ensuring alignment among its components to improve its effectiveness in boosting tourism demand in travel and tourism organizations.